(-14)=j-(-24)

Simple and best practice solution for (-14)=j-(-24) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-14)=j-(-24) equation:


Simplifying
(-14) = j + -1(-24)
-14 = j + -1(-24)

Multiply -1 * -24
-14 = j + 24

Reorder the terms:
-14 = 24 + j

Solving
-14 = 24 + j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '-1j' to each side of the equation.
-14 + -1j = 24 + j + -1j

Combine like terms: j + -1j = 0
-14 + -1j = 24 + 0
-14 + -1j = 24

Add '14' to each side of the equation.
-14 + 14 + -1j = 24 + 14

Combine like terms: -14 + 14 = 0
0 + -1j = 24 + 14
-1j = 24 + 14

Combine like terms: 24 + 14 = 38
-1j = 38

Divide each side by '-1'.
j = -38

Simplifying
j = -38

See similar equations:

| -11-w=-36 | | 4(2x-3)-3(x-2)+2=4-(x-7) | | y+2x=27 | | S-11=(-34) | | (z^2-2iz)*(z^2+25)=0 | | 3x+3=-25 | | -11=s+5 | | (-11)=13+x | | 15/25=y/30 | | (-15)+g=(-5) | | (2c+9)(c+5)= | | f(x)=6x^3+8x^2+3 | | 6(1-2x)-x=-46 | | B-17=-38 | | 6+2x=5-(7x) | | J+13=37 | | a^2+4ab+4b^2=0 | | M+(-10)=(-2) | | -3a+8=2 | | 4x-3y=52 | | (-17)=(-9)+q | | f(x)=a^3-3a^2-9 | | 2.25=3/4(b-5) | | 17+n=4 | | 6x-x^2+16= | | (-22)+j=(-24) | | 72.8=7(m+3.1) | | 4x+23=75 | | (2c+9)x(c+5)= | | 3[m-1.2]=9 | | h-8+2(h-8)=72 | | 47=19-4x |

Equations solver categories